Incidence of Hypertension-Related Emergency Department Visits in the United States, 2006–2012 - McNaughton, Candace D. (Am J Cardiol, 2015)
Hypertension is a common chronic condition, but the burden of emergency department visits due to hypertension and associated patient and hospital characteristics are not well described. The goals of this study were to 1) establish the burden of hypertension-related emergency department visits, estimated by the total number, proportion of adult visits, and population-based rate, 2) evaluate for change over time, and 3) identify associated patient and hospital characteristics. The Nationwide Emergency Department Sample from 2006 to 2012 was used to identify hypertension-related emergency department visits (ICD-9 CM codes 401 through 405, inclusive, and 437.2), and this was linked to US Census Bureau July population estimates to determine population-based rates for each study year. Negative binomial regression was performed to determine whether rates of hypertension-related emergency department visits changed over time. A total of 165,946,807 hypertension-related emergency department visits occurred during the seven-year study period (23.6% of all adult ED visits), and hypertension was the primary diagnosis for 6,399,088 (0.9% of all adult ED visits). The estimated yearly incidence rate rose 5.2% per year (incident rate ratio 1.052, 95% confidence interval 1.044 to 1.061, p<0.001) for hypertension-related visits, and 4.4% per year (incidence rate ratio 1.044, 95% confidence interval 1.038 to 1.051, p<0.001) for ED visits with a primary diagnosis of hypertension. Over the same time, the proportion hospitalized declined and the proportion of visits rose at safety net hospitals and among uninsured patients. In conclusion, these data indicate that hypertension-related ED visits are common and rising.